Light regulates expression of brain-derived neurotrophic factor mRNA in rat visual cortex. - Castrén, E (1992)
Specific sensory input has profound transient and long-lasting effects on the function of corresponding sensory cortical areas both during development and in adulthood. To study whether neurotrophic factors might play a role in such processes, we investigated the effects of light on the nerve growth factor and brain-derived neurotrophic factor (BDNF) mRNA levels in rat visual cortex. Keeping adult rats in the dark or preventing normal activity of retinal ganglion cells by intraocular injection of tetrodotoxin significantly decreased the levels of BDNF mRNA in the visual cortex but not in other cortical areas. Exposure to light after a period in darkness rapidly restored the mRNA to control levels. These alterations in visual input had no effect on nerve growth factor mRNA. The mRNA of trkB, the putative signal-transducing receptor unit for BDNF, was also decreased in darkness, although less than BDNF mRNA. BDNF mRNA levels increased in the visual cortex of newborn rats after eye-opening. This increase is retarded, although not completely abolished, by rearing the pups in darkness. Thus, the levels of BDNF mRNA are rapidly regulated by sensory input during development and in adulthood. BDNF may therefore play an important role in formation and in activity-dependent modulation of specific connections in the visual cortex.